1985
DOI: 10.1172/jci112049
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effect of 3,3',5'-triiodothyronine in cultured growth hormone-producing rat pituitary tumor cells. Evidence for a unique mechanism of thyroid hormone action.

Abstract: Physiologic levels of 3,3',5'-triiodothyronine (rT3) are generally believed to have minimal metabolic effects in the pituitary gland and other tissues. In the present studies, the regulatory role of rT3 and other thyroid hormones on iodothyronine 5'-deiodinase (15D) activity was studied in a growth hormoneproducing rat pituitary tumor cell line (GH3 cells). O5D activity was thiol-dependent and displayed nonlinear reaction kinetics suggesting the presence of two enzymatic processes, one having a low Michaelis c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Because it was reported that D2 activity was present in GH3 rat pituitary tumor cells (20,21), effects of DEX and cAMP on D2 expression in GH3 cells were also studied. As shown in Fig.…”
Section: Effects Of Camp and Dex On D2 Expression In Gh3 Cellsmentioning
confidence: 99%
“…Because it was reported that D2 activity was present in GH3 rat pituitary tumor cells (20,21), effects of DEX and cAMP on D2 expression in GH3 cells were also studied. As shown in Fig.…”
Section: Effects Of Camp and Dex On D2 Expression In Gh3 Cellsmentioning
confidence: 99%
“…In addition, gene transcription can be measured based on the modulation of basal GH and PRL secretion in GH3 cells, which is related directly to regulation of GH and PRL mRNA expressions (Tamura et al, 2000). Furthermore, GH3 cells possess both deiodinase 1 (Dio 1) and 2 (Dio 2) activity (St Germain, 1985;Mori et al, 2007), and are responsive to T3 (Baur et al, 1997). Both deiodinases have an important role for maintaining local T3 levels in the brain and pituitary in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…and rT 3 in particular, are also capable of inhibiting the activity of this enzyme in cell cultures in the absence of thyroid hormones (22)(23)(24).…”
Section: Tlmentioning
confidence: 97%